The effects of the nursing self-esteem enhancement (Nurse) program to the self-esteem of Filipino abused women - Gavino, Ma. Irma B.
This study attempted to explore the women's perception of womanhood and their self-esteem. It tested an intervention measure, the Nursing Self-Esteem Enhancement (NURSE) Program to enhance self-esteem so that in the end women may be assisted to take action and tend for themselves.Jurgen Habermas' Critical Social Theory, Feminism and feminist principles were used as framework for the study.The study made used of the sequential methodological triangulation. There were two phases: the qualitative phase using the Critical Social Theory approach and the quantitative phase using the correlational and the quasi-experimental non-equivalent control group design. A total of 30 respondents in the National Home for Women called The Haven acted as study participants. There were 14 interviews conducted for the qualitative phase while in the quantitative phase there were 15 participants for both the study and control groups. Instruments used were the Demongraphic Data and Information Sheet, Interview Guide and the Self-Esteem Scale. Data analysis for the Critical Social Theory was used for the qualitative phase. Statistical treatment of data include frequencies, means, standard deviations, multiple correlation, two-way repeated measures design, least significant difference (LSD) and step-wise multiple regression. The results showed that the essence of womanhood is being a good mother and a good wife. Women's role as mothers were upheld and sacrifices on the part of the women were important to preserve their role as mother and wife. Women still hold the traditional view that they are subservient to their husband. Abuse was perceived to be wrong but women can do little about the situation. As measured by the Self-Esteem Scale the level of self-esteem of women respondents was moderate. No relationship was found between the roles that women play and their status in society to their levels of self-esteem.The important finding of the study was that raising consciousness among women is necessary to uncover the distortion of low status of women and the cultural tolerance of violence. The intervention measure tested, the NURSE Program affected an increase in the levels of self-esteem of the respondents after four weeks, hence, nurses may utilize this intervention measure to enhance abused women's self-esteem. It is hoped that abused women will have the increased capacity to act and make decisions.